“Comprehensive Analysis of Factors Influencing Recurrence and Survival in Glioblastoma: Implications for Treatment Strategies”: A Single Center Study - Ahmed Bendari; Sunder Sham; Hamed Hammoud; Oana Vele; Brett Baskovich; David Huang; Alaa Bendari; Rachel Saks; Reham Al-Refai; Tasneem Bendari; Layth Kataw; Fnu Kiran; et al. (Journal of Molecular Pathology)
Glioblastoma is a highly aggressive malignancy affecting the brain and central nervous system. It is the most common malignant primary brain tumor, yet its prognosis remains poor. Median survival typically ranges from around 13 months with standard treatment to up to 19.9 months in some recent clinical trials. Despite advances in treatment, the aggressive nature of glioblastoma continues to present significant challenges for improving patient outcomes. This study aimed to analyze various biological, radiological, and molecular factors associated with glioblastoma recurrence and to estimate survival outcomes. A total of 104 glioblastoma patients diagnosed between January 2017 and September 2022 were included. Patient demographics, treatment received, and molecular characteristics were obtained from the Electronic Patient Record (EPR). Tumor molecular characteristics were analyzed using the OnkoSight Advanced CNS NGS panel. Statistical analyses were performed to develop a prognostic model for glioblastoma recurrence and estimate survival rates. Among the patients, 65.4% had no recurrence, with a mean age of 63 years. No gender or BMI differences were observed, but ages <60 years were associated with recurrence. Radiological findings showed no significant differences in tumor size, necrosis, site, or focality. In multivariate analysis, the female gender, obesity, old age (>60 years), or bifocal tumors were associated with decreased glioblastoma recurrence. However, factors like tumor site, size, necrosis, MGMT promoter methylation, and EGFR alteration showed no significant association with recurrence. Median survival was 12 months, with older age significantly associated with shorter survival. Tumor sizes >4 cm showed shorter survival trends but not statistically significantly. Patients who lived longer experienced more tumor recurrence incidents. Standard or non-standard treatments were associated with longer median survival compared to no treatment. Our findings provide insights into factors influencing glioblastoma recurrence and survival. Age, gender, and tumor characteristics play pivotal roles in recurrence. Understanding these factors could aid in optimizing treatment strategies and improving patient outcomes. However, further multicentric investigations are needed to validate these findings. This study emphasizes the importance of considering biological and radiological factors in clinical decision-making for glioblastoma cases.